Overexpression of Medicago sativa TMT elevates the α-tocopherol content in Arabidopsis seeds, alfalfa leaves, and delays dark-induced leaf senescence. (August 2016) - Jiang, Jishan; Jia, Huili; Feng, Guangyan; Wang, Zan; Li, Jun; Gao, Hongwen; Wang, Xuemin
Highlights: A γ-tocopherol methyltransferase (γ-TMT) gene MsTMT was isolated from alfalfa ( Medicago sativa L.). Overexpression of MsTMT in Arabidopsis altered the composition of vitamin E in seeds and leaves. Overexpression MsTMT increased α-tocopherol and α-tocotrienol content in leaves of alfalfa. Leaf senescence was inhibited in MsTMT overexpression alfalfa under dark. Overexpression of MsTMT did not decrease the quality traits in alfalfa. Abstract: Alfalfa ( Medicago sativa L.) is a major forage legume for livestock and a target for improving their dietary quality. Vitamin E is an essential vitamin that animals must obtain from their diet for proper growth and development. γ-tocopherol methyltransferase (γ-TMT), which catalyzes the conversion of δ- and γ-tocopherols (or tocotrienols) to β- and α - tocopherols (or tocotrienols), respectively, is the final enzyme involved in the vitamin E biosynthetic pathway. The overexpression of M. sativa L.'s γ-TMT ( MsTMT ) increased the α-tocopherol content 10–15 fold above that of wild type Arabidopsis seeds without altering the total content of vitamin E. Additionally, in response to osmotic stress, the biomass and the expression levels of several osmotic marker genes were significantly higher in the transgenic lines compared with wild type. Overexpression of MsTMT in alfalfa led to a modest, albeit significant, increase in α-tocopherol in leaves and was also responsible for a delayed leaf senescence phenotype. Additionally, the crude protein content was increased, while the acid and neutral detergent fiber contents were unchanged in these transgenic lines. Thus, increased α-tocopherol content occurred in transgenic alfalfa without compromising the nutritional qualities. The targeted metabolic engineering of vitamin E biosynthesis through MsTMT overexpression provides a promising approach to improve the α-tocopherol content of forage crops.